Causality Then and Now: Al Ghazali and Quantum Theory (American Journal of Islam and Society, 1993)
Ate appearances deceiving? Do objects behave the way they do becauseGod wills it? Ate objects impetmanent and do they only exist becausethey ate continuously created by God? According to a1 Ghazlli, theanswers to all of these questions ate yes. Objects that appear to bepermanent are not. Those relationships commonly tefemed to as causalare a result of God’s habits rather than because one event inevitably leadsto another. God creates everything in the universe continuously; if Heceased to create it, it would no longer exist.These ideas seem oddly naive and unscientific to people living in thetwentieth century. They seem at odds with the common conception of thephysical world. Common sense says that the universe is made of tealobjects that persist in time. Furthermore, the behavior of these objects isreasonable, logical, and predictable. The belief that the univetse is understandablevia logic and reason harkens back to Newton’s mechanical viewof the universe and has provided one of the basic underpinnings ofscience for centuries. Although most people believe that the world is accutatelydescribed by this sort of mechanical model, the appropriatenessof such a model has been called into question by recent scientificadvances, and in particular, by quantum theory. This theory implies thatthe physical world is actually very different from what a mechanicalmodel would predit.Quantum theory seeks to explain the nature of physical entities andthe way that they interact. It atose in the early part of the twentieth centuryin response to new scientific data that could not be incorporated successfullyinto the ptevailing mechanical view of the universe. Due largely ...